An Introduction to Criticism of the Cultural-Based Approach to Foreign Policy: A Critical Analysis of Language, Discourse and Foreign Policy - Maghsood Ranjbar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article reviews the book "Language, Discourse and Foreign Policy" by Mr. Majid Adibzadeh, considering that the author's approach is cultural and discursive, and genealogical. The foreign policy of the Islamic Republic of Iran is based on anti-discourse discourses from the 1330s onwards. The purpose of this paper is to assess the cultural views and attitudes toward foreign policy in general, and the view of the author of this book is in particular. The basic question of this article is whether culturally-oriented attitude theoretically can explain politics in Iran in general and foreign policy of Iran   in particular. The hypothesis of this article is that the cultural-oriented approach is reductive; instead of focusing on the role of power and structure, it focuses on the culture as a cause while that is an dependent variable. For this reason, the critical review of the cultural-oriented attitude to foreign policy and critique of the writer's view of the foreign policy of the Islamic Republic of Iran is the main focus of this article.